Pattern of Haemarthrosis in Haemophilia - ZahidaQasim, NadeemIkram, KhalidHassan (Journal of Rawalpindi Medical College, 2013)
Background: To study the pattern of haemarthrosis and its related complications in patients of Haemophilia A and B. Methods: Fifty one patients of Haemophilia A and B were evaluated on the basis of patient`s demographic data, history (family, medication, past) and parameters like age, clinical features (pallor, number of joint involved, ankylosis and pain). Blood complete picture, coagulation screening tests, bleeding time, PT, APTT, mixing studies and factor assays were documented. Results: Haemarthrosis was seen in 86% of the patients, 15.7% patients had single joint involvement. Three to six joints were involved in 43.1%of patients while 11 (21.6%) patients had no joint involvement. Right Knee was the most commonly involved joint(53%).. Ankylosis was documented in 12%. Eight percent were using crutches. Haemarthrosis was directly proportional to severity of disease and children under the age of 5 years did not show significant arthropathy. Conclusion: Haemarthrosis with joint deformities is the commonest manifestation of haemophilia. Treatment with factor concentrate, prophylaxis and physiotherapy can help to prevent new bleeds and allow the synovitis to resolve.